Phosphorus in Some Indian Soybean Varieties and its Association with Oil Characteristics - Mandlik, Ashish (Asian Journal of Chemistry, 2016)
The seeds of thirteen promising soybean varieties were obtained from four agroclimatic regions of Central India in order to study the variation of total available phosphorus and lipid phosphorus in Indian soybeans. It was observed that the planting location makes a great effect on the availability of total phosphorus in soybean seeds whereas the varietal variation observed is insignificant. The total phosphorus in soybean seed ranges from 588 to 684 mg per 100 g seed. The planting location as well as variety, both the parameters have considerable influence on lipid phosphorus (i.e., the phosphorus in extracted lipid of soybean seeds) on seed basis and range from 259 to 414 mg per 100 g of soybean. The lipid phosphorus in soybean oil observed was having statistically significant influence only of planting location whereas the genetic control observed was insignificant. The lipid phosphorus in soybean seed observed was varied in the range of 1450 to 2010 mg per 100 g of soybean oil. All these parameters observed have a positive association with refractive index and specific gravity of soybean oil while the free fatty acid observed has a negative correlation with lipid phosphorus in soybean oil.